Struktur Komunitas dan Anatomi Rumput Laut di Perairan Teluk Awur, Jepara dan Pantai Krakal, Yogyakarta - Rini Pramesti; AB. Susanto; Wilis A Setyati; Ali Ridlo; Subagiyo Subagiyo; Yohanes Oktaviaris (Jurnal Kelautan Tropis, 2016)
Seaweed has ecological benefits as well as economic value. Waters condition of Awur Bay and Krakal Beach supported this plant’s growth. There’s not yet the latest information about the vegetation. Utilization is still limited on some specieses. Tourist and inhabitant’s activities who take this plant would give impact to this plant’s vegetation. Therefore, it’s necessary to have data collecting, monitoring, and controlling at both of location. This research was aim to inventarisasi of seaweed for morphologic and anatomic characteristics at both of location. The research of method is explorative descriptive. The results showed that the amount of seaweed which was found at Awur Bay based on the morphology characteristics consist of two divisions was Chlorophyta (3 species) and Phaeophyta (5 species). Beside that, the amount of seaweed which was found at Krakal Beach based on the morphology characteristics consist of three divisons was Chlorophyta (4 species), Phaeophyta (2 species) and Rhodophyta (11 species). Three types of cell (anatomy) i.e. epidermis, kortex and medulla. The results of seaweed which found at Krakal Beach are density, frequency, cover percentage, important value index, and ecology index was taller than Awur Bay.Rumput laut bermanfaat secara ekologis maupun ekonomis. Kondisi perairan Teluk Awur, Jepara dan Pantai Krakal, Yogyakarta mendukung tumbuhan ini dapat tumbuh. Pemanfaatannya masih terbatas pada jenis tertentu. Aktivitas wisatawan dan penduduk sekitar yang mengambil tumbuhan ini akan berpengaruh sehingga perlu dilakukan penelitian tentang struktur komunitas di kedua lokasi tersebut. Penelitian ini bertujuan untuk mengetahui struktur komunitas, inventarisasi jenis baik secara morfologi dan anatomi. Metode yang digunakan yaitu metode deskriptif eksploratif. Hasil penelitian menunjukkan jumlah jenis rumput laut yang ditemukan di Teluk Awur terdiri dari dua divisi yaitu Chlorophyta (3 jenis) dan Phaeophyta (5 jenis). Jumlah jenis yang ditemukan di Pantai Krakal terdiri dari tiga divisi yaitu Chlorophyta (4 jenis), Phaeophyta (2 jenis) dan Rhodophyta (11 jenis). Tiga jenis sel penyusun thallus yaitu sel epidermis, korteks dan medulla. Struktur komunitas yang ditemukan di Pantai Krakal meliputi kepadatan, frekuensi, persentase penutupan, indeks nilai penting, dan indeks ekologi lebih tinggi daripada di Teluk Awur.